KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) KONSUMEN MILENIAL DALAM MENGKONSUMSI SAYURAN ORGANIK (Suatu Kasus pada Warung Sehat 1000 Kebun, Kota Bandung) - Handoko, Bagus Imran Saptadji; Setiawan, Iwan (Universitas Galuh Ciamis, 2021)
Non-infectious diseases are now the dominant cause of deaths in Indonesia and the numbers are increasing each year. One of the causes of these non-infectious diseases is unhealthy consumption patterns, such as consuming a massive amount of fast foods. Increased awareness within the general public especially the millennial generation about the importance of health is shown through the emergence of a sense of caring for a healthy life by consuming organic food. Organic foods that are mostly found today are organic vegetables, which have an important role for health, thus they are often consumed as a complement to staple foods. Based on these issues, this study aims to determine how willing are the millennials to pay for organic vegetables at Warung Sehat 1000 Kebun. This study is conducted through quantitative research and survey methods using questionnaires as the instrument to conduct interviews. The analysis method used in this study is the validity test, reliability test, descriptive statistical analysis, multiple linear regression analysis and Contingent Valuation Method (CVM). The results showed that the factors that most influenced the willingness of consumers who created millennials were psychological factors, which significantly affected consumers' willingness to consume organic vegetables.